Ultrasound-assisted Extraction of Carbohydrates from Microalgae - Fabrizio Di Caprio; Pietro Altimari; Francesca Pagnanelli (Chemical Engineering Transactions, 2021)
Microalgae are a promising new source of carbohydrates usable for several industrial applications in the food and biomaterial sector. Previous works on carbohydrate extraction from microalgae were mainly carried out by using destructive chemical hydrolysis, aiming at the extraction of simple sugars. Here in this work, a physical ultrasonication method was investigated to develop a process to extract microalgal carbohydrates in their polysaccharide form, as starch. To this end, different operative parameters were investigated: biomass concentration (3-6 g L-1), microalgae strain (Tetradesmus obliquus and Chlorella sp.), extraction time, amplitude (21-90 µm) and the configuration of the ultrasonication system (cyclic treatment, pulsed and continuous). The highest extractions were attained with higher amplitude (90 µm). The pulsed ultrasonication (ton/toff = 0.2) worked remarkably better than the continuous one, allowing to attain about 3 folds more carbohydrate extraction yield and consuming 6 folds less kWh per kg of extracted carbohydrates. The higher yield achieved with pulsed ultrasonication was related with a lower drop in the applied power during the ultrasonication treatment, which was -65 % with the continuous system and only -31 % with the pulsed one. The ultrasonication treatment induced a temperature increase up to 70 °C, that caused starch gelatinization and its solubilization in the recovered aqueous solution. Future studies should investigate better the effect of the ton/toff ratio, to limit the dead times (toff) of the process. The specific energy consumption was still too high for many practical applications; however, future optimizations on biomass concentration and operative temperature are expected to reduce remarkably the energy demand of the process.